Environmental justice and pesticides - Atreya, Kishor; Kattel, Kanchan; Sapkota, Anisha; Gartaula, Hom Nath (Routledge, 2024)
The use of pesticides is increasing in Nepal when growing vegetables. This study investigated the distribution, recognition, and management of the benefits and risks of pesticides among men, women, and various social groups. The study finds that exposure to pesticides during critical stages of life poses elevated health risks to women. Despite participating in training programs and having a greater understanding of the dangers of pesticides, privileged caste men still show a lower level of compliance with safety measures when it comes to handling these substances. On the contrary, women who are less informed, but perceive higher risks, adopt stronger safety precautions. The Brahmin, Chhetri, Thakuri (BCT) community greatly benefits from opportunities such as integrated pest management (IPM) training. However, most of their farmland has been leased by the indigenous group, Danuwar, increasing the risk of exposure to pesticides. Traditional fishing practice in Danuwar was significantly affected by the harmful effects of pesticides. In the case of Dalits, small farms protect them from excessive exposure to pesticides. We see that conventional methods of extension and awareness raising are insufficient when it comes to addressing pesticide-health dynamics. It will be crucial to implement customized training, education, and awareness programs that are comprehensive, inclusive, and accessible to account for historical biases related to caste and gender. The interconnection between agriculture and health should be a top priority for policymakers to develop a fair agricultural system that benefits all people equally and the environment.